Diversidad de escarabajos coprófagos (Coleoptera Scarabaeidae) en un paisaje urbanizado en el sur del Ecuador - Quezada Ríos, Noelia Magdalena (2018)
Abstract:In this work, was studied the communities of dung beetles (Coleoptera: Scarabaeidae) in four different land uses of Loja city, Forest (Bo), Forest-Pasture (BP), Pasture (Pa) and Urban (Ur). The individuals were collected for each land use by pitfall traps, baited with pig dung. For each land use, individuals were collected by using pitfall traps, baited with pig dung. In Ur land use, no individuals were found. While in the three remaining land uses, 307 individuals belonging to three genera and five species were recorded. The most representative species in Bo and Pa were Onthophagus curvicornis, while for BP were Uroxys aff. frankenbergeri. In disturbed areas, such as, Pa, greater abundance was observed but less diversity and richness compared to other land uses. Forest (Bo) had the highest diversity. According to the species accumulation curves, the sampling efforts for Bo and Pa were 100%, while for BP it is necessary to make a greater effort. Using Jaccard's similarity index, the composition of dung beetles forms four groups, being the most silimar forest (Bo) and pasture (BP)